Analysis of clinical features of 231 cases with pernicious placenta previa: A retrospective cohort study. Issue 11 (19th March 2021) - Li, Ping; Tang, Yabing; Jiang, Yurong; Li, Dezhong
Abstract : Abstract: Pernicious placenta previa (PEPP) is a severe complication of late pregnancy, which might result in adverse maternal-fetal outcome. To explore the application value of placenta accreta score (PAS) for PEPP and its association with maternal-fetal outcome. In this retrospective cohort study, the clinical data of PEPP patients were analyzed. According to the ultrasonic PAS, patients were grouped into 3 groups: scores ⩽5, a scores between 6 and 9, and scores ≥10. The clinical data, intraoperative and postoperative outcomes were collected. Receiver operating characteristic (ROC) curves were used to evaluate the performance of PAS in disease severity evaluation. Multivariate logistic and linear regression analysis were performed to assess associations of PAS with intraoperative and postoperative outcomes. A total of 231 patients were enrolled. There were significant differences in intraoperative, postoperative and neonatal outcomes, such as operation time, bladder repair, ICU admission, postoperative hospitalization days, operation complications, Apgar score of newborns in 1 minute and premature delivery among the 3 groups (all P < .05), while the worst outcomes were found in those with a score ≥ 10 (all P < .05). According to ROC curves, scores <5.5, between 5.5 and 7.5, and >7.5 indicated placenta accreta, placenta increta and placenta percreta, respectively. PAS was independently associated with longer time of operation, surgical complications, intraoperative bleeding volume, and postoperative hospitalization days (all P < .05). Placenta accreta score might help with PEPP subtype diagnosis and predict the maternal-fetal outcome of PEPP patients. Abstract : Supplemental Digital Content is available in the text